Gender Specific English Advertisements - Arakelyan, Ruzanna; Petrosyan, Ani (Armenian Folia Anglistika, 2020)
Advertising is a worldwide phenomenon nowadays that has gained the attention and interest of a large number of individuals in different societies around the world. Advertising is not only an “ideal tool” for reaching people economically, but also a device of attaining and maintaining contact with people socially, culturally, politically and even psychologically. As men and women perceive various social phenomena and often react to certain situations in quite distinct ways, it is also vividly expressed in the ways they perceive the effectiveness of advertising language. This is also conditioned by the fact that men and women create different imagery from the advertisements they see. This confirms the fact that ad specialists should analyze how they choose the target viewers and what language they should use to focus on them. Thus, gender is one of the main segmentation variables for the advertiser, and a significant factor that makes it interesting to advance the study of how gender differences are manifested in the language of advertisements.
Keywords: advertising; gender language; gender differences and perceptions; communicative power of language